A new method to calibrate ionospheric pulse dispersion for UHE cosmic ray and neutrino detection using the Lunar Cherenkov technique - McFadden, R.; Ekers, Ronald; Roberts, P. (Elsevier, 2012)
UHE particle detection using the lunar Cherenkov technique aims to detect nanosecond pulses of Cherenkov emission which are produced during UHE cosmic ray and neutrino interactions in the Moon's regolith. These pulses will reach Earth-based telescopes dispersed, and therefore reduced in amplitude, due to their propagation through the Earth's ionosphere. To maximise the received signal to noise ratio and subsequent chances of pulse detection, ionospheric dispersion must therefore be corrected, and since the high time resolution would require excessive data storage this correction must be made in real time. This requires an accurate knowledge of the dispersion characteristic which is parameterised by the instantaneous Total Electron Content (TEC) of the ionosphere. A new method to calibrate the dispersive effect of the ionosphere on lunar Cherenkov pulses has been developed for the LUNASKA lunar Cherenkov experiments. This method exploits radial symmetries in the distribution of the Moon's polarised emission to make Faraday rotation measurements in the visibility domain of synthesis array data (i.e. instantaneously). Faraday rotation measurements are then combined with geomagnetic field models to estimate the ionospheric TEC. This method of ionospheric calibration is particularly attractive for the lunar Cherenkov technique as it may be used in real time to estimate the ionospheric TEC along a line-of-sight to the Moon and using the same radio telescope.